IMPLEMENTASI KEBIJAKAN INSENTIF KESEHATAN DI BERBAGAI NEGARA: IMPLEMENTASI KEBIJAKAN INSENTIF KESEHATAN DI BERBAGAI NEGARA - Dimas Nurwidi (Yayasan Pendidikan Medika Indonesia, 2025)
Introduction: Health incentive policies have become an important focus in efforts to improve the quality of healthcare services and public health outcomes in various countries. These incentives can take the form of financial incentives, such as bonuses or allowances, as well as non-financial incentives, such as awards or recognition. Objective: This study aims to collect, analyze, and present empirical evidence on the implementation of health incentive policies across various countries through a systematic review. The objectives of this research are expected to provide a deeper understanding of the types of incentive policies in place, the factors influencing the success of their implementation, and their impact on healthcare provider performance and public health outcomes. Method: This research method uses a systematic review method to collect, filter, and analyze data related to the implementation of health incentive policies in various countries Result: The result section presents the findings of the research in a clear and systematic manner. It reports the outcomes of data analysis, including any statistical analyses performed. Results are often presented using tables, figures, or graphs to enhance clarity and facilitate interpretation. This section objectively presents the empirical evidence obtained from the study without interpretation or speculation. Conclusion: Health incentive policies have great potential to improve the quality of health services. However, their effectiveness is highly dependent on the right design and contextual support and adjusting policies based on local needs.